Some considerations on orthogonality, strict separation theorems and applications in Hilbert spaces - Ferreira, M. A. M. (2022)
After presenting some structural notions on Hilbert spaces, which constitute fundamental support for this work, we approach the goals of thechapter. First,studyaboutconvexsets,projections,andorthogonality, whereweapproachtheoptimizationprobleminHilbertspaceswithsome generality. Then the approach to Riesz representation theorem in this ﬁeld, important in the rephrasing of the separation theorems. Then we give a look to the strict separation theorems as well as to the main results of convex programming: Kuhn-Tucker theorem and minimax theorem. These theorems are very important in the applications. Moreover, the presented strict separation theorems and the Riesz representation theorem have key importance in the demonstrations of Kuhn-Tucker and minimax theorems and respective corollaries.